2002
DOI: 10.1161/01.res.0000014451.75415.36
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Dysfunction With Coronary Microembolization

Abstract: Abstract-Coronary microembolization results in progressive myocardial dysfunction, with causal involvement of tumor necrosis factor-␣ (TNF-␣). TNF-␣ uses a signal transduction involving nitric oxide (NO) and/or sphingosine. Therefore, we induced coronary microembolization in anesthetized dogs and studied the role and sequence of NO, TNF-␣, and sphingosine for the evolving contractile dysfunction. Four sham-operated dogs served as controls (group 1). Eleven dogs received placebo (group 2), 6 dogs received the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(45 citation statements)
references
References 65 publications
1
44
0
Order By: Relevance
“…Using DMR+Q550 pathological image pattern analysis instrument to analyze slices stained by HBFP, five microscopic visual fields (×100) were randomly sampled from each slice for observation, using Leica Qwin analysis software (Germany) and the planar area method to measure the infraction zone, expressing as area percent of bulk analysis slice and averaging. [13]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using DMR+Q550 pathological image pattern analysis instrument to analyze slices stained by HBFP, five microscopic visual fields (×100) were randomly sampled from each slice for observation, using Leica Qwin analysis software (Germany) and the planar area method to measure the infraction zone, expressing as area percent of bulk analysis slice and averaging. [13]…”
Section: Methodsmentioning
confidence: 99%
“…[10] Clinical findings show that metoprolol could play its roles of anti-inflammation and anti-apoptosis to improve cardiac function in condition of ischemic cardiomyopathy. [8,11,12] The function of metoprolol in the treatment of CME is not entirely clear, but myocardial apoptosis certainly occurs after CME[13] and metoprolol can inhibit myocardial apoptosis. Therefore, this study aims to observe the effect of metoprolol on myocardial apoptosis and caspase-3 activation after CME in rats, and to explore how metoprolol can prevent myocardial injury caused by CME, and to provide theoretical basis for the clinical prevention and treatment of CME.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the aggregate amount of infarction involved a small area (<5%) of microembolized myocardium in pigs or dogs, as indicated by the typical inflammatory responses with increases in TNF-α expression and leukocyte infiltration [6,7,20,21]. Our preliminary studies showed that a post-CME inflammatory response occurred as a result of the upregulation of TNF-α expression in the myocardium [10,11].…”
Section: Discussionmentioning
confidence: 53%
“…Our preliminary studies showed that a post-CME inflammatory response occurred as a result of the upregulation of TNF-α expression in the myocardium [10,11]. It has been well established that excessive TNF-α expression is derived from the surviving cardiomyocytes surrounding microinfarcts in autocrine or paracrine patterns [6] and is responsible for the detrimental effect on progressive contractile dysfunction [6,7,8,20,22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation